2015
DOI: 10.22226/2410-3535-2015-1-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Discrete breathers with hard and soft type of nonlinearity in 1D Morse lattices with long-range interactions

Abstract: 1Мирнинский политехнический институт (филиал) Северо-Восточного федерального университета, ул. Тихонова 5/1, 678175, Мирный, Россия 2 Институт проблем сверхпластичности металлов РАН, ул. Степана Халтурина 39, 450001, Уфа, Россия † sash-alex@yandex.ru, ‡ elena.a.korznikova@gmail.com В последнее время в области изучения дискретных бризеров наблюдается переход от теоретических исследований, связанных с доказательством их существования в упрощенных нелинейных системах, к поиску долгоживущих бри-зеров в реальных об… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We considered the value α = 5, for which the equilibrium interatomic distance is a = 0.98813 at the potential cutoff radius of 5.5a. We note that the Morse potential was often used for the simulation of different properties of discrete breathers in crystals [23][24][25][26][27][28][29][40][41][42][43][44][45][46].…”
Section: Nonlinear Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…We considered the value α = 5, for which the equilibrium interatomic distance is a = 0.98813 at the potential cutoff radius of 5.5a. We note that the Morse potential was often used for the simulation of different properties of discrete breathers in crystals [23][24][25][26][27][28][29][40][41][42][43][44][45][46].…”
Section: Nonlinear Phenomenamentioning
confidence: 99%
“…The authors of [38] could excite only the discrete breathers with the soft type of nonlinearity, considering a diatomic chain with a gap in the phonon spectrum. It was shown later that discrete breathers with the hard type of nonlinearity can exist in two-and threedimensional crystals with Morse interaction [39][40][41][42][43][44][45][46]. The reason is that the effect of the increase in the average interatomic distances in the core of the discrete breathers can be suppressed to some extent in crystals of dimension higher than unity and, thus, the hard core of the interatomic potential makes a larger contribution to the dynamics of the system than the soft tail.…”
mentioning
confidence: 99%
“…However, in [6] a possibility of existence of DB with hard type of nonlinearity and with frequencies above the phonon spectrum was demonstrated by means of molecular dynamics modeling for Ni and Nb. Later the possibility of the existence DB above the phonon spectrum of the crystal was confirmed in our works [7][8][9][10][11][12] for the case of two-dimensional (2D) monoatomic crystal with Morse interaction potential. The aim of this work is to investigate the effect of the rigidity of the Morse potential on the properties of DB in 2D monoatomic crystal model.…”
Section: Introductionmentioning
confidence: 75%
“…By now, a large volume of works has been performed to analyze properties of DB in various crystalline materials, particularly, the results of the molecular dynamics studies have been reported in . Several works have been devoted to the study of DB in model crystals with Morse interatomic potentials [4][5][6][7], while other works to the study of DB in graphene and related materials [8][9][10]. In the work [8], for the first time, DB in a crystalline body has been studied with the help of DFT theory, using graphane as an example.…”
Section: Introductionmentioning
confidence: 99%